Glycerol-based retrievable heterogeneous catalysts for single-pot esterification of palm fatty acid distillate to biodiesel - Hazmi, Balkis; Beygisangchin, Mahnoush; Rashid, Umer; Wan Mokhtar, Wan Nur Aini; Tsubota, Toshiki; Alsalme, Ali; Ngamcharussrivichai, Chawalit (Multidisciplinary Digital Publishing Institute, 2022)
The by-product of the previous transesterification, glycerol was utilised as an acid catalyst precursor for biodiesel production. The crude glycerol was treated through the sulfonation method with sulfuric acid and chlorosulfonic acid in a reflux batch reactor giving solid glycerol-SO3H and glycerol-ClSO3H, respectively. The synthesised acidic glycerol catalysts were characterised by various analytical techniques such as thermalgravimetric analyser (TGA), infrared spectroscopy, surface properties adsorption-desorption by nitrogen gas, ammonia-temperature programmed desorption (NH3-TPD), X-ray diffraction spectroscopy (XRD), elemental composition analysis by energy dispersive spectrometer (EDX) and surface micrographic morphologies by field emission electron microscope (FESEM). Both glycerol-SO3H and glycerol-ClSO3H samples exhibited mesoporous structures with a low surface area of 8.85 mm2/g and 4.71 mm2/g, respectively, supported by the microscopic image of blockage pores. However, the acidity strength for both catalysts was recorded at 3.43 mmol/g and 3.96 mmol/g, which is sufficient for catalysing PFAD biodiesel at the highest yield. The catalytic esterification was optimised at 96.7% and 98.2% with 3 wt.% of catalyst loading, 18:1 of methanol-PFAD molar ratio, 120 °C, and 4 h of reaction. Catalyst reusability was sustained up to 3 reaction cycles due to catalyst deactivation, and the insight investigation of spent catalysts was also performed.